The impact of societal performance on the financial performance of companies listed on the Casablanca Stock Exchange: explanation by accounting and stock market measures - IBENRISSOUL , Nafii; JOUALY , Dounia (Revue Internationale des Sciences de Gestion, 2024)
The problem of the link between Social Performance (SP) and Financial Performance (FP) has attracted the attention of several researchers in several fields. A review of the literature on this relationship is subject to considerable controversy, mainly due to the confusion surrounding attempts to operationalize social performance, the lack of uniformity in the assessment of financial performance, and the methodological anomalies found in the analysis of the relationship. Several studies have been conducted to prove the existence or non-existence of this link, with mixed results. This article attempts to shed light on this issue while presenting a synthesis of the work that has focused on verifying this causal link between the two constructs. The results obtained raise, on the one hand, the existence of a link between SP and FP and, on the other hand, the absence of a relationship.